2016
DOI: 10.1007/s11695-016-2084-5
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Multivitamin Supplements After Sleeve Gastrectomy

Abstract: NCT02620137.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…We found lowered vitamin B1 levels in nine patients (7.3%) throughout the study period, but none showed clinical symptoms. This differs from RYGB patients in whom such deficiencies hardly occur [7,8]. Theoretically, this could be explained by the higher risk of minimized intake and vomiting after SG compared to a RYGB.…”
Section: Vitamin B1 Deficiencymentioning
confidence: 84%
See 3 more Smart Citations
“…We found lowered vitamin B1 levels in nine patients (7.3%) throughout the study period, but none showed clinical symptoms. This differs from RYGB patients in whom such deficiencies hardly occur [7,8]. Theoretically, this could be explained by the higher risk of minimized intake and vomiting after SG compared to a RYGB.…”
Section: Vitamin B1 Deficiencymentioning
confidence: 84%
“…There are several factors that put patients at risk for developing nutritional deficiencies after SG, including reduced food intake, decreased hydrochloric acid and intrinsic factor secretion, vomiting, poor food choices, and food intolerance [7,21]. Yet, others believe that SG has minimal impact on nutrient status [3] and that maintenance of MVS more than 3 months postoperatively seems to be of no benefit [8]. According to Ruiz-Tovar et al, once a patient is able to eat all kinds of food, additional vitamin and mineral supplementation can be discontinued [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although RYGB was found to be the gold standard procedure, the most commonly performed procedure in many countries is currently the sleeve gastrectomy [22,23]. Laparoscopic sleeve gastrectomy is a restrictive procedure that is characterized by the removal of most of the fundus of the stomach without alteration of intestinal absorption; it is considered to be relatively safe with low morbidity [24,25,26]. The changes of the gastrointestinal tract resulting from such interventions are supposed to also affect the absorption of orally administered drugs.…”
Section: Introductionmentioning
confidence: 99%